2021
DOI: 10.1039/d1dt00792k
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive “ON–OFF–ON” dual optical sensor for the detection of Cu(ii) ion and triazole pesticides based on novel BODIPY-substituted cavitand

Abstract: The synthesis with full structural characterization including elemental analysis and 1H, 13C, 11B and 19F NMR, FT-IR and MALDI-TOF spectral data, along with florescent sensing behavior of a new resorcin[4]arene...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This study presents a detailed investigation of the photophysical, photochemical and electrochemical properties of BODIPY compounds (1)(2)(3)(4)(5)(6)(7). We demonstrated that adding pyrene moieties expands the p-conjugated system, contributing to an enhanced singlet oxygen quantum yield.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This study presents a detailed investigation of the photophysical, photochemical and electrochemical properties of BODIPY compounds (1)(2)(3)(4)(5)(6)(7). We demonstrated that adding pyrene moieties expands the p-conjugated system, contributing to an enhanced singlet oxygen quantum yield.…”
Section: Discussionmentioning
confidence: 93%
“…3 4,4 0 -Difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) compounds have attracted the interest of researchers in recent years due to their excellent photophysical characteristics, strong UV absorption, emission spectra with distinct and well-defined peaks of fluorescence, and good solubility in a wide range of solvents. [4][5][6][7][8] The photophysical properties of these compounds can be changed by adding different groups to different positions of the BODIPY core, and large Stokes shifts or fluorescence intensities can be monitored using mechanisms such as FRET (Fo ¨rster or fluorescence resonance energy transfer), ICT (intramolecular charge transfer), and PET (photoinduced electron transfer). 9 In addition, the incorporation of heavy halogen atoms (such as Br and I) into the BODIPY core is the most popular strategy for enhancing the excited state (S 1 -T 1 ) intersystem crossing (ISC).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of new fluorescent chemosensors for Cu 2+ ion has drawn continuous interest during the past decades. The main progress in this area has been well reviewed ( Cao et al, 2019 ; Sivaraman et al, 2018 ; Udhayakumari et al, 2017 ; Liu et al, 2017 ), and many fluorescent chemosensors for Cu 2+ ion based on various fluorophores such as coumarin ( Zhang et al, 2019 ), Bodipy ( Ömeroğlu et al, 2021 ), rhodamine ( Fernandes and Raimundo, 2021 ), Schiff base ( Singh et al, 2020 ), pyrene ( Kowser et al, 2021 ), and 1,3,4-oxadiazole ( Wang, et al, 2018 ) have been reported by different research groups. Among these fluorescent chemosensors, the 1,3,4-oxadiazoles have drawn special interest due to their electron-deficient nature, high photoluminescence quantum yield, and excellent chemical stability, and have found practical applications in the fields of organic light-emitting diodes ( Meng et al, 2020 ) and liquid crystals ( Han et al, 2013 ; Han et al, 2015 ; Han et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%